Culpable leaders, trust, emotional exhaustion, and identification during a crisis. Issue 8 (7th November 2016) - Kovoor-Misra, Sarah; Gopalakrishnan, Shanthi
Abstract : Purpose: The purpose of this paper is to investigate followers' judgments of the culpability of their leaders and the organization's external stakeholders in causing a crisis. The authors study the differences in effects of these judgments on their trust toward their leaders, their emotional exhaustion, and their levels of organizational identification. Design/methodology/approach: Using the survey method the authors collected data from 354 individuals from an organization that filed for bankruptcy. Respondents' comments also provided qualitative data that was used to triangulate the findings. Findings: The authors find that individuals' judgments that their leaders were culpable led to reduced trust, increased emotional exhaustion, and contrary to expectations reduced organizational identification. Therefore, it appears that in situations of perceived leader culpability during a crisis, followers tightly couple their leaders with the organization as a whole. In contrast, their judgments that external stakeholders were culpable were associated with increased trust toward their leaders, increased organizational identification, and they had no relationship with their levels of emotional exhaustion. The analysis of the qualitative data provides some insights into their judgments and the dependent variables. Research limitations/implications: Organizational members' judgments of culpability are important factors that should be considered in crisis management research, and in research on trust, emotional exhaustion, and organizational identification. A limitation of the study is that it is cross-sectional in nature. Therefore, future research could test the findings in a longitudinal study. Practical implications: Leaders need to understand the judgments of their followers during an organizational crisis. These judgments have implications for when and how leaders can mobilize their followers and the leadership tasks during crisis containment. Originality/value: Extant research tends to focus on the judgments of external stakeholders during a crisis. This study is one of the first to examine the effects of internal stakeholders' judgments of culpability for causing a crisis on their trust, emotional exhaustion, and organizational identification. Further, existing empirical studies on followers' attributions during a crisis tend to be laboratory based. The study provides empirical evidence from individuals in an actual organization in crisis.